2004
DOI: 10.1159/000074670
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cariporide (HOE642) on Myocardial Infarct Size and Ventricular Arrhythmias in a Rat Ischemia/Reperfusion Model: Comparison with Other Drugs

Abstract: The effects of pretreatment with cariporide on myocardial infarction and ventricular arrhythmias in a rat model of ischemia/reperfusion were compared with those of nicorandil, propranolol, and nifedipine. Each drug was administered intravenously before coronary occlusion. Cariporide at 0.1, 0.3, and 1 mg/kg significantly reduced the infarct size (infarct mass/risk mass) from 28 ± 4% (vehicle control value) to 9 ± 3, 9 ± 3, and 5 ± 2%, respectively. Propranolol at 2.5 mg/kg also significantly reduced the infarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The arrhythmogenicity in our experimental model appeared to be more severe compared to the similar rat model with a protocol of 20 min ischemia/2 h reperfusion [10] , in part due to the longer period of ischemia and reperfusion, despite which most of the VPBs, VT and VF were observed to occur throughout the period of ischemia and up to the fi rst 10 min of reperfusion in our model as reported by others [10,23] . KR-32568 dose-dependently and signifi cantly reduced the occurrence of all three types of ventricular arrhythmia during ischemia/reperfusion as refl ected in total number of VPBs, total events and duration of VT and VF, these effects being in line with those for cariporide, a well-characterized prototype NHE-1 selective inhibitor in the similar rat model of ischemia/reperfusion heart injury [10,30] , probably due to its peculiar mode of action as described in the following section. The differential antiarrhythmic effects on VPBs, VT and VF appear to depend on the types of drugs, the multiplicity of their action and the variable mechanisms of arrhythmogenesis [31].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The arrhythmogenicity in our experimental model appeared to be more severe compared to the similar rat model with a protocol of 20 min ischemia/2 h reperfusion [10] , in part due to the longer period of ischemia and reperfusion, despite which most of the VPBs, VT and VF were observed to occur throughout the period of ischemia and up to the fi rst 10 min of reperfusion in our model as reported by others [10,23] . KR-32568 dose-dependently and signifi cantly reduced the occurrence of all three types of ventricular arrhythmia during ischemia/reperfusion as refl ected in total number of VPBs, total events and duration of VT and VF, these effects being in line with those for cariporide, a well-characterized prototype NHE-1 selective inhibitor in the similar rat model of ischemia/reperfusion heart injury [10,30] , probably due to its peculiar mode of action as described in the following section. The differential antiarrhythmic effects on VPBs, VT and VF appear to depend on the types of drugs, the multiplicity of their action and the variable mechanisms of arrhythmogenesis [31].…”
Section: Discussionsupporting
confidence: 73%
“…0.05). These cardioprotective effects of KR-32568 were comparable to those of a prototype selective NHE-1 inhibitor cariporide demonstrated in various animal models of ischemia/reperfusion heart injury [10,20,[30][31][32] .…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…We found that reduction of vasospasm from nifedipine treatment partially reversed cardioprotection. Nifedipine administration, itself, is not thought to be effective at reducing infarct size, although it may improve left ventricular function following ischemia [25][26][27]. Therefore, it is possible that nifedipine may be inhibiting cardioprotection via a cardiomyocyte specific mechanism that requires calcium.…”
Section: Discussionmentioning
confidence: 99%